2014
DOI: 10.1007/s12603-014-0001-y
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of chronic co-morbid medical conditions in older residents of U.S. nursing homes: Differences between the sexes and across the agespan

Abstract: Objective There are limited data on combinations of co-morbid conditions to guide efforts to improve therapeutic strategies in patients with multiple co-morbid conditions. To some extent, this may be due to limited data on combinations of co-morbid conditions in patient groups. Our goal was to determine the most common co-morbid medical conditions in older residents of U. S. nursing homes and identify sex differences in prevalences and changes across the agespan of nursing residents. Design Cross sectional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 23 publications
4
69
1
3
Order By: Relevance
“…Other individual‐level factors that vary across nursing home residents—their beliefs about their appropriate roles (e.g., passive vs. active) and their functional and cognitive capacities—affect their motivation, willingness, and ability to engage in PDCP (Carman et al, 2013). The issue of cognitive capacity presents particular challenges to PDCP in LTC settings where dementia—which is characterised by global cognitive deterioration, including impairments in memory, language expression and comprehension, and the ability to determine goals or carry through with plans to achieve goals—is prevalent (Moore, Boscardin, Steinman, & Schwartz, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…Other individual‐level factors that vary across nursing home residents—their beliefs about their appropriate roles (e.g., passive vs. active) and their functional and cognitive capacities—affect their motivation, willingness, and ability to engage in PDCP (Carman et al, 2013). The issue of cognitive capacity presents particular challenges to PDCP in LTC settings where dementia—which is characterised by global cognitive deterioration, including impairments in memory, language expression and comprehension, and the ability to determine goals or carry through with plans to achieve goals—is prevalent (Moore, Boscardin, Steinman, & Schwartz, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…8 Lacking the cognitive reserve to separate speech from noise, residents with cognitive impairment may be particularly vulnerable to failure to understand speech in noisy environments. Other conditions common among nursing home residents (eg, depression and chronic pain 14 ) are likely to further decrease motivation to invest listening effort.…”
Section: Nursing Homes Are Difficult Listening Situations and Many Rmentioning
confidence: 99%
“…This too is unlikely; in fact, long-stay residents probably have a higher risk of hearing loss than their same-aged peers in the community due to the association between hearing loss and chronic conditions such as cardiovascular disease, diabetes and dementia, which are highly prevalent among nursing home residents. 14 …”
Section: A National Estimate Of the Prevalence Of Hearing Loss Among mentioning
confidence: 99%
“…Such findings might be influenced by differences between sexes, because females make up a larger proportion of residents, are older and generally have a higher disease burden than males [16, 17]. However, analyses on hospitalizations of nursing home residents are usually not presented stratified by sex and such differences do not receive much attention in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is also not clear whether differences are present in male and female residents with comparable health status or if predictors of hospitalization differ between sexes. Such differences between sexes do not receive much attention in research on nursing home residents, although it has been shown that patterns of care needs, chronic medical conditions and service utilization differ between male and female residents [16, 17]. However, understanding sex-dependent differences is essential to identify oversupply or undersupply of health services and to optimise care.…”
Section: Introductionmentioning
confidence: 99%